Efektifitas Program Kartu Indonesia Pintar Terhadap Pemenuhan Kebutuhan Pendidikan Tinggi Bagi Mahasiswa Kurang Mampu Di Universitas Negeri Surabaya - Yoggy Pratama; Zainal Fatah; Nihayatus Sholichah; Ika Devy Pramudiana (Journal of Innovative and Creativity, 2026)
The high cost of higher education in Indonesia remains a major obstacle for students from low-income families to continue their studies at universities. This condition prompted the government to launch the Indonesia Smart College Card Program (Kartu Indonesia Pintar Kuliah or KIP-K) as an affirmative policy aimed at expanding equitable and inclusive access to higher education. The program is designed to reduce financial burdens by providing tuition waivers and living allowances for economically disadvantaged students with strong academic potential. Universitas Negeri Surabaya (UNESA) is one of the state universities with the highest number of KIP-K recipients in Indonesia, making it a relevant setting to examine the program’s effectiveness. This study aims to analyze the effectiveness of the KIP-K Program in fulfilling the educational needs of underprivileged students at UNESA and to identify its supporting and inhibiting factors. The study employs a descriptive qualitative approach, with data collected through in-depth interviews and observations involving four informants: two KIP-K recipients and two non-recipients. Data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that the KIP-K Program at UNESA is relatively effective based on Soetrisno’s (2016) five indicators of effectiveness: program comprehension, goal attainment, target accuracy, timeliness, and tangible change. The program has positively influenced students’ learning motivation, academic discipline, and financial independence. However, several challenges remain, including delayed fund disbursement, unequal dissemination of information, and insufficient monitoring of fund utilization. Strengthening the monitoring system, improving distribution mechanisms, and enhancing program outreach are recommended to ensure the program’s sustainability and to promote equitable access to higher education in Indonesia